(3GdJQbjI HGdENJjGQ ai GdhXjaI GdYGeI (B: s (3OQGSI ebGQfI (B/ s - (3gOi CMeO UGdM eMeO s; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3Ef fXGe GdhXjaI GdYGeI jYO MLQ GdRGhjI dUQM GdfgVI HGdfSHI dCi OhdI hPdc deG JeKdI GdhXjaI ef CgejI aGFbI dfLGM GdOhdI HUaI NGUI Hd hdfLGM Ci JfXje BNQ HUaI NGUI Hd hdfLGM Ci JfXje BNQ HUaI YGeI hdCf GdehXa GdYGe gh bhGe fLGM Ci eQab hef Ke fLGM GdOhdI cdgG aEfI ef GdVQhQi Cf jfWhi fXGe GdhXjaI GdYGeI Ydi eGjMaQ geI GdehXa hjOaYI Edi GdELJgGO ai YedI hGdJaGfi ajI(B.(3hGdJQbjI JYO ef Cge GdOhGaY GdJi JMK GdehXa Ydi EJbGf YedI hHPd CbUi LgO ajI deG JeKdI ef JLSjO dWehM GdehXa hQZHJI ai GdQbi HMce chfI EfSGfs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B241-246s
Keywords: (3GdbGfhf GdYGes; (3GdJQbjI HGdENJHGQs; (3GdJQbjIs; (3GdhXjaI GdYGeIs; (3GdbGfhf GdGeQjcis; (3GdGNJjGQ GdeWdb ddJQbjIs; (3GdGNJjGQ GdebjO ddJQbjIs; (3GLQGAGJ GdJQbjI HGdGNJjGQs; (3GdQbGHI GdbVGFjI Ydi GdJQbjI HGdGNJjGQs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes